Implementation of the E-Government-Based Village Asset Management System (SIPADES) Policy in Ketapang Village, Tanggulangin District, Sidoarjo Regency: Implementasi Kebijakan Aplikasi Sistem Pengelolaan Aset Desa (SIPADES) berbasis E-Government di Desa Ketapang, Kecamatan Tanggulangin, Kabupaten Sidoarjo - Rheina Adinda Zahrani; Isnaini Rodiyah (Universitas Indo Global Mandiri, 2026)
Purpose : This study aims to describe and analyze the implementation of the e-government-based SIPADES application policy in Ketapang Village and identify factors that support and hinder its implemention. Design/methodology/approach : This study employed a descriptive qualitative method, collecting data through field observations, interviews, and documentation. The data analysis was guided by George C. Edward III’s theoretical framework on policy implementation, which emphasizes four key components: communication, resources, disposition, and bureaucratic structure. Findings : The results of the study suggest that the implementation of SIPADES in Ketapang Village has not been ideal due to inadequate socializing, data loss during updates, and unstable internet connections. However, the village officials remain committed through the provision of facilities and manual recording, but the workload is still concentrated on the Village Secretary. Practical Implication : These findings form the basis for the village government and the the Village Community Empowerment Office to improve technical assistance, improve communication regarding application updates, strengthen digital infrastructure, and equalize SIPADES operational tasks. Originality/value : This research provides a fresh viewpoint on the implementation of SIPADES in regions impacted by disasters, highlighting the crucial role of external influences in determining the success of e-government initiatives—an aspect that has been minimally explored in earlier studies.